Conductance and dielectric anisotropy properties of 4-cyano-4?-hexylbiphenyl-salicylaldimine compound composite liquid crystal exhibiting large positive dielectric anisotropy - Yakuphanoğlu, Fahrettin; Bilgin-Eran, B.; Ocak, H.; Oweimreen, G. A. (Elsevier Science Bv, 2007)
The electronic properties of 4-cyano-4'-hexylbiphenyl and salicylaidimine compound 1 liquid crystals have been investigated. The polarizing microscopy and differential scanning calorimetry results show that chiral salicylaidimine compound 1 exhibits enantiotropic smectic A* and SmC* mesophases. The novel 4-n-hexyl-4'-cyanobiphenyl/salicylaidimine compound 1 composite showed an extremely large positive dielectric anisotropy. The dielectric anisotropy of the LCs changes from positive type to negative type. The critical frequency f(c), values of dielectrical anisotropy for 4-n-hexyl-4'-cyanobiphenyl and salicylaldimine compound 1 LCs were found to be 630.50 and 813.01 kHz, respectively. The splay elastic constant K-11 values of the liquid crystals were calculated and the doping of salicylaldimine compound 1 into 4-cyano-4'-hexylbiphenyl liquid crystal increases the splay elastic constant of 6CB. The parallel conductivity all values of the liquid crystals are higher than that of perpendicular conductivity sigma perpendicular to values and conductivity of the 4-cyano4'-hexylbiphenyl decreases with doping of salicylaldimine compound 1. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: liquid crystal; dielectric anisotropy; salicylaldimine; elastic constants